From coercion to consent: social identity, legitimacy, and a process model of police procedural justice, 2018-2021 - Stott, Clifford John T. (UK Data Service, 2023)
This data collection includes quantitative data obtained during the three research strands of this project. Consent for publicly sharing the qualitative data is not in place and retrospective consent is not feasible, and accordingly a waiver has been granted for these data. Keele University strand: One interview study and one wider ethnographic study (including field notes). These data includes sensitive personally identifying information. Consent for publicly sharing this data is not in place and retrospective consent is not feasible, and accordingly a waiver has been granted for these data. London School of Economics strand: One study utilised The European Social Survey (ESS) which is a social scientific endeavour to map the attitudes, beliefs and behaviour patterns of the various populations in Europe. ESS is listed in the Registry of Research Data Repositories re3data.org University College London strand: 1. One survey study involved presenting the results from two UK-based studies that explore the identity dynamics of procedural justice theory. These data are available via related resources. 2. Another survey study assessed the extent to which police procedural justice, effectiveness, legitimacy, and perceived risk of sanction predict compliance with the law among people experiencing homelessness. Two hundred people (87% male, 49% aged 45–64, 37% White British) experiencing homelessness on the streets of an inner London borough completed a survey that included measures of procedural justice, police legitimacy, perceived risk of sanction, morality, and compliance with the law. These data are available via related resources. 3. Another study used two text-based vignette experiments and one video study, and our aims are threefold: (1) to explore the influence of suspect race in how people respond to police use of force; (2) to test the interaction between participant ethnicity and suspect race; and (3) to understand what attitudes and beliefs influence how people respond to police use of force. These data are available via related resources. 4. Another study used two online experiments to test whether different force options affected judgments about the acceptability of police action and to explore the role of trust and legitimacy in people's judgments. These data are available via related resources. 5 An ethnographic study includes sensitive personally identifying information. Consent for publicly sharing this data is not in place and retrospective consent is not feasible, and accordingly a waiver has been granted for these data. The concept of legitimacy lies at the heart of democratic policing: in a democratic society, police must seek and maintain public support by acting impartially, using coercion proportionately, and persuading the citizenry that they are an institution that is entitled to be obeyed. Yet, there are multiple highly marginalised communities for whom perceptions of police illegitimacy, non-compliance, conflict, and experiences of police coercion are the norm. With its central focus on fairness, legitimacy, identification between police and public, and normative compliance, Procedural Justice Theory (PJT) is a useful model to understand how to improve police community relations. But there are several aspects of the theory that limit its policy relevance in relation to policing marginalised groups - i.e. those with whom police have most contact. First, PJT research focuses on the general population and only infrequently on sub-populations. While we know much about how people in general understand and read policing, and the role of fairness in such understandings, we know less about how general experiences feed across to those parts of the population who have most at stake in their interactions with officers, who have long histories of problematic relations with police, and/or are increasingly the focus of police strategic priorities (e.g. safeguarding, radicalisation, anti-social behaviour, protest groups). Second, there is a heavy reliance in extant research on survey data and correlational analysis, and there is a pressing need for laboratory-based experiments to establish causal relations and delineate the subjective processes linking procedural justice, legitimacy, and law-related behaviour. Third, there is a related failure to address the nature and role of social identity, intergroup relations, and the dynamics of police-public interaction as mediators of fairness, legitimacy, and compliance. This project will address these limitations by developing two parallel programmes of research. First, we will use ethnographic methods to obtain direct semi-structured observational data of a series of police interactions with marginalised groups across a range of contexts. We will conduct interviews with the people involved in those encounters (police, 'citizen', observer) to interpret how encounters were experienced, processed, and judged. When arrests (or other forms of criminal justice action) take place, we will develop longitudinal data by tracking those individuals through the criminal justice processes, undertaking a further series of interviews and questionnaires with various stakeholders involved in that process. We will also have access to statistical data concerning the nature and context of the encounters (e.g. stop and search statistics). Second, we will translate a series of police-public encounters into a fully immersive Virtual Reality (VR) programme that participants will experience via headsets to engineer a series of experimental studies. Both experimental and ethnographic strands will explore the following questions: 1) What specific role(s) does 'social identity' play in perceptions of procedural fairness? 2) What contextual factors shape people's perceptions of the fairness of police activity and how do these change through and within interaction? 3) Are marginalized/excluded groups attuned to the fairness of police behaviour in different ways, and how do the dynamics of interaction with police officers shape or undermine this marginalisation? 4) What effect does the experience of police procedural (in)justice have on the subsequent behaviour of the individuals concerned? By addressing these questions the project will advance our theoretical understanding of the ways police can move away from coercion toward a consent-based approach among highly marginalised and 'difficult to reach' groups; theoretical knowledge that will provide applied benefit for a range of different stakeholders.